Sunspot observations at Kawaguchi Science Museum: 1972 – 2013. Issue 1 (26th December 2022) - Hayakawa, Hisashi; Suzuki, Daisuke; Mathieu, Sophie; Lefèvre, Laure; Takuma, Hitoshi; Hiei, Eijiro
Abstract: Individual sunspot observations have formed a ground basis of international sunspot number, a unique reference for long‐term solar variability in the centennial timescale. The original datasets were subjected to exploitations and analyses upon the recalibrations of the sunspot number series. In this context, this study reviewed and analysed original sunspot records and their databases in the Kawaguchi Science Museum (KSM) in Japan. KSM hosts sunspot drawings and logbooks from 1972 to 2013. This dataset has a longer chronological coverage than what was known to the scientific community (1981–2010). These records have been digitized and publicized in a museum database, which allows users to access individual sunspot drawings and numerical data in KSM logbooks. These records are highly homogeneous as a single observer's dataset (Hitoshi Takuma), who used a 15‐cm refractor at the Kawaguchi Juvenile Museum in 1972–2003 and a 20‐cm refractor at KSM in 2003–2013. We also reviewed the Takuma data series, his monthly observation days (21.3 days/month), sunspot number in the whole disk and each hemisphere, and sunspot positions in a butterfly diagram. We also assessed Takuma's data stability in comparison with the international sunspot number and reference datasets of the SILSO. Takuma's data appear stable until 2003, when he changed the observation site and instrument. His data stability was quantitatively compared with the SILSO reference datasets, confirming the substantial long‐term stability of the data and establishing its reliability as an alternative reference for sunspot number recalibration. Abstract : This article visualises a database for Hitoshi Takuma's sunspot observations and background metadata.